Risk factors for urological complications following living donor renal transplantation in children. (29th October 2017) - ElSheemy, Mohammed S.; Ghoneima, Waleed; Aboulela, Waseem; Daw, Kareem; Shouman, Ahmed M.; Shoukry, Ahmed I.; Soaida, Sherif; Salah, Doaa M.; Bazaraa, Hafez; Fadel, Fatina I.; Hussein, Ahmed A.; Habib, Enmar; et al.
Abstract: The aim of this study was to detect possible risk factors for UC and UTI following pediatric renal Tx and effect of these complications on outcome. One hundred and eight children who underwent living donor Tx between 2009 and 2015 were retrospectively included. Extraperitoneal approach was used with stented tunneled extravesical procedure. Mean recipient age was 9.89 ± 3.46 years while mean weight was 25.22 ± 10.43 kg. Seventy‐three (67.6%) recipients were boys while 92 (85.2%) were related to donors. Urological causes of ESRD were present in 33 (30.6%) recipients (14 [13%] posterior urethral valve, 16 [14.8%] VUR, and 3 [2.8%] neurogenic bladder). Augmentation ileocystoplasty was performed in 9 (8.3%) patients. Mean follow‐up was 39.3 ± 17.33 months. UC were detected in 10 (9.3%) children (leakage 4 [3.7%], obstruction 3 [2.8%], and VUR 3 [2.8%]) while UTIs were reported in 40 (37%) children. After logistic regression analysis, UC were significantly higher in children with cystoplasty (44.4% vs 6.1%; P  =   .001). UTIs were significantly higher in girls (51.4% vs 30.1%; P  =   .001) and in children with urological causes of ESRD (51.5% vs 30.7%; P  =   .049). UC and UTI were not significantly associated with increased graft loss or mortality. UC were significantly higher in children with cystoplasty while UTIs were significantly higher in girls and children with urological causes of ESRD. Presence of UC did not affect the rate of graft loss or mortality due to its early detection and proper management.